Portrait of John Steinbeck - Bill Epridge (Life Magazine):::Creator::::::::::::; Hayman, Lee Richard (collector):::Contributor::::::::::::
John Steinbeck, smoking.For original, John Steinbeck: 1902-1968.' Time 1968-12-27. 61+.